Debridement, antimicrobial therapy, and implant retention (DAIR) as curative surgical strategy for acute periprosthetic hip and knee infections: a summary of the position paper from the European Bone & Joint Infection Society (EBJIS) - I. K. Sigmund; M. Wouthuyzen-Bakker; T. Ferry; W. J. Metsemakers; W. J. Metsemakers; M. Clauss; A. Soriano; A. Soriano; A. Soriano; R. Trebse; R. Sousa (Journal of Bone and Joint Infection)
This is a summary of our position paper on debridement, antimicrobial therapy, and implant retention (DAIR) procedures as curative treatment strategy for acute periprosthetic hip and knee infections. It includes the defined indications as well as the contraindications for DAIR procedures when eradication/cure is intended, based on the currently available literature. Risk factors which need to be considered during the decision-making process are described. Additionally, we give an overview of important surgical and medical considerations in the management of acute PJI patients treated with DAIR.